2017
DOI: 10.1088/2053-1591/aa77d8
|View full text |Cite
|
Sign up to set email alerts
|

Partial electronic conductivity of nanocrystalline Na2O2

Abstract: was prepared from the coarse-grained material (97%, Sigma Aldrich, No. 223417) using a high-energy planetary mill (Fritsch Pulverisette 7 (premium line)) operated at a rotation speed of 500 rpm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[ 35 ] Hence, also by considering results in literature presented so far, it is very likely that electron transport is not coupled with ion transport, as it may happen in some other materials with poor ion conducting properties. [ 36 ] The low activation energy associated with electronic conductivity is very likely the key reason for this decoupling. Having a low activation energy, the electron mobility is significantly less influenced by the temperature than the ionic mobility.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35 ] Hence, also by considering results in literature presented so far, it is very likely that electron transport is not coupled with ion transport, as it may happen in some other materials with poor ion conducting properties. [ 36 ] The low activation energy associated with electronic conductivity is very likely the key reason for this decoupling. Having a low activation energy, the electron mobility is significantly less influenced by the temperature than the ionic mobility.…”
Section: Resultsmentioning
confidence: 99%
“…In both R-4 and R-7, the diffusion rate of Na + is the critical factor to affect the decomposition of the discharge products. It is reported that Na 2 CO 3 possesses much higher Na + ionic conductivity (∼10 −12 S cm −1 ) 50,51 than Na 2 O 2 (∼10 −13 S cm −1 ), 52 which may offer faster kinetics for the decomposition of Na transformation advanced from the surface toward the core until complete decomposition (Figure 1c,e,g), while the latter remained its crystalline state almost unchanged (Figure 7b). The small grain size and poor crystallinity might be another probable reason for the complete decomposition of Na 2 CO 3 in the Na−O 2 /CO 2 −CNT nanobattery during the charging process.…”
Section: Discussionmentioning
confidence: 95%
“…In both R- and R-, the diffusion rate of Na + is the critical factor to affect the decomposition of the discharge products. It is reported that Na 2 CO 3 possesses much higher Na + ionic conductivity (∼10 –12 S cm –1 ) , than Na 2 O 2 (∼10 –13 S cm –1 ), which may offer faster kinetics for the decomposition of Na 2 CO 3 than Na 2 O 2 in the in situ experiments. In addition, the main charge products of the Na–O 2 /CO 2 –CNT battery and the Na–O 2 –CNT battery were Na 2 CO 3 and Na 2 O 2 , respectively, and the morphology and crystallinity of which are obviously different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Araujo et al also used DFT to investigate charge migration in α-Na 2 O 2 and found that the conductivity is dominated by the diffusion of hole polarons. These results are consistent with the experimental studies of Dunst et al and Philipp et al who independently investigated the temperature-dependent conductivity of α-Na 2 O 2 . Dunst et al observed an electronic conductivity around 10 –14 S/cm at room temperature and an activation energy from 193 to 373 K of ∼1.06 eV.…”
Section: Introductionmentioning
confidence: 94%